2012
DOI: 10.1007/s12603-012-0074-4
|View full text |Cite
|
Sign up to set email alerts
|

Screening for delirium within the interrai acute care assessment system

Abstract: The interRAI AC delirium screening strategy is a valid measure of delirium in older subjects in acute medical wards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 25 publications
0
14
2
Order By: Relevance
“…For example, the rate of prevalent delirium in this study is lower than the rates reported in two previous Australian studies (18% and 22%) [9, 10], while the rate of incident delirium is both substantially higher and lower than rates previously reported in Australian research (2% and 25%) [9, 11]. While methodological differences are likely to underpin some of the different findings, important differences in patient characteristics across the studies are also likely to account for the different rates.…”
Section: Discussioncontrasting
confidence: 90%
“…For example, the rate of prevalent delirium in this study is lower than the rates reported in two previous Australian studies (18% and 22%) [9, 10], while the rate of incident delirium is both substantially higher and lower than rates previously reported in Australian research (2% and 25%) [9, 11]. While methodological differences are likely to underpin some of the different findings, important differences in patient characteristics across the studies are also likely to account for the different rates.…”
Section: Discussioncontrasting
confidence: 90%
“…This tool was chosen as it is imbedded in a standardised comprehensive geriatric assessment 20 and has previously shown optimal psychometric properties. 21 It screens for acute change in mental status and a change in cognition across a day. Patients were identified as having CI if they met the cut-off point for impairment on one of the applied formal tests (OMCT or the interRAI Delirium Screen) ( Table 1) or if there was a formal prior diagnosis of chronically impaired cognition (including dementia or mild cognitive impairment).…”
Section: Selection Of Participantsmentioning
confidence: 99%
“…The Orientation Memory Concentration Test (OMCT) 38 was used for cognitive impairment without delirium, and the interRAI delirium screen was used for delirium identification. 30 The OMCT is a paper-based screening tool that evaluates a patient's orientation, registration, and attention. Tested against a reference test (Mini-Mental State Examination [MMSE]), this tool had 95% sensitivity and 65% specificity in an older (≥65 years) ED population.…”
Section: Days])mentioning
confidence: 99%
“…Using the DSM-IV criteria for delirium, this test was found to be 90% sensitive and 69% specific for detecting delirium in an older (≥70 years) population admitted to acute medical wards. 30 The interRAI delirium screen was used in this study as it was part of a larger standardized assessment tool by interRAI, which collected data across a range of geriatric syndromes, including delirium. The interRAI delirium screen was administered during the first contact with the researcher and at least once before ED discharge.…”
Section: Days])mentioning
confidence: 99%
See 1 more Smart Citation